Feeding dynamics and reproductive biology of the obtuse barracuda Sphyraena obtusata (Cuvier, 1829) from Ratnagiri, central west coast of India - Ranaware, Shraddha D.; Vivek H. Nirmale; Bhaskar P. Bhosale; santosh Y. Metar; Prakash E. Shingare (Indian Journal of Fisheries, 2023)
The obtuse barracuda Sphyraena obtusata (Cuvier, 1829) is a commercially important food fish belonging to the family Sphyraenidae and landed mostly as trawl bycatch along Ratnagiri. Investigations were carried out on the species with respect to the length-weight relationship, condition factor, morphometrics, feeding and reproductive biology. The length-weight relationship showed positive allometric growth in males, females and pooled individuals. All morphometric measurements showed a high degree of correlation with total length. The gut content analysis revealed S. obtusata to be a carnivore fish feeding mainly on fish juveniles, fish scales, crustaceans and cephalopod appendages. The male:female sex ratio was found to be 1:0.90. Gonado-somatic index (GSI), maturity and ova diameter studies indicated that S. obtusata has a prolonged spawning season with individuals spawning twice in a season. Absolute fecundity ranged from 68355 to 310615 eggs with an average of 137783 eggs. The mean length at sexual maturity for females was found to be 22.92 cm. Keywords: Carnivorous fish, Fish biology, Life history, Trophodynamics, Tropical fisheries